INTEGRATION BLOCKS’ GRAVITY EFFECTS ON RUSSIAN FOREIGN TRADE - N. Chernov (Вестник университета)
In the article the analysis of Russian foreign trade interactions with main integration associations with stable economic relations based on gravity model is presented. The results of calculations of econometrical model and evaluations of Russian foreign trade cooperation with various integration blocks are given. Changes of foreign trade interactions with integration associations in dynamics both for total trade turnover and turnover without mineral fuel, oil and oil products trade are considered. Conclusions of Russian trade orientation are given.